Croton lechleriExtracts as Green Corrosion Inhibitors ofAdmiralty Brass in Hydrochloric Acid - Cevallos Morillo, Carlos (2021)
moleculesArticleCroton lechleriExtracts as Green Corrosion Inhibitors ofAdmiralty Brass in Hydrochloric AcidCarlos Cevallos-Morillo1, Pablo Cisneros-Pérez2, Roxana Llive2, Marvin Ricaurte3, Carlos Reinoso4,Miguel Angel Meneses5, Maria del Cisne Guamán5and Alex Palma-Cando3,* Citation:Cevallos-Morillo, C.;Cisneros-Pérez, P.; Llive, R.; Ricaurte,M.; Reinoso, C.; Meneses, M.A.;Guamán, M.d.C.; Palma-Cando, A.Croton lechleriExtracts as GreenCorrosion Inhibitors of AdmiraltyBrass in Hydrochloric Acid.Molecules2021,26, 7417. https://doi.org/10.3390/molecules26247417Academic Editors: Soumen Mandal,Han-Seung Lee and JitendraKumar SinghReceived: 17 November 2021Accepted: 3 December 2021Published: 7 December 2021Publisher’s Note:MDPI stays neutralwith regard to jurisdictional claims inpublished maps and institutional affil-iations.Copyright:© 2021 by the authors.Licensee MDPI, Basel, Switzerland.This article is an open access articledistributed under the terms andconditions of the Creative CommonsAttribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).1Facultad de Ciencias Químicas, Universidad Central del Ecuador, Francisco Viteri s/n y Gato Sobral,Quito 170129, Ecuador; cacevallosm@uce.edu.ec2Universidad Regional Amazónica Ikiam, Tena 150102, Ecuador; pablo.cisneros@ikiam.edu.ec (P.C.-P.);wendy.llive@ikiam.edu.ec (R.L.)3Grupo de Investigación Aplicada en Materiales y Procesos (GIAMP), School of Chemical Sciences andEngineering, Yachay Tech University, Hda. San Josés/n y Proyecto Yachay, Urcuquí100119, Ecuador;mricaurte@yachaytech.edu.ec4School of Physical Sciences and Nanotechnology, Yachay Tech University, Hda. San Josés/n y ProyectoYachay, Urcuquí100119, Ecuador; creinoso@yachaytech.edu.ec5Departamento de Química y Ciencias Exactas, Universidad Técnica Particular de Loja, Loja 110150, Ecuador;mameneses@utpl.edu.ec (M.A.M.); mcguaman@utpl.edu.ec (M.d.C.G.)*Correspondence: apalma@yachaytech.edu.ecAbstract:Croton lechleri,commonly known as Dragon’s blood, is a tree cultivated in the northwestAmazon rainforest of Ecuador and Peru. This tree produces a deep red latex which is composedof different natural products such as phenolic compounds, alkaloids, and others. The chemicalstructures of these natural products found inC. lechlerilatex are promising corrosion inhibitors ofadmiralty brass (AB), due to the number of heteroatoms andπstructures. In this work, three differentextracts ofC. lechlerilatex were obtained, characterized phytochemically, and employed as novel greencorrosion inhibitors of AB. The corrosion inhibition efficiency (IE%) was determined in an aqueous0.5 M HCl solution by potentiodynamic polarization (Tafel plots) and electrochemical impedancespectroscopy, measuring current density and charge transfer resistance, respectively. In addition,surface characterization of AB was performed by scanning electron microscopy, energy-dispersiveX-ray spectroscopy, and X-ray photoelectron spectroscopy techniques. Chloroform alkaloid-richextracts resulted in IE% of 57% at 50 ppm, attributed to the formation of a layer of organic compoundson the AB surface that hindered the dezincification process. The formulation of corrosion inhibitorsfromC. lechlerilatex allows for the valorization of non-edible natural sources and the diversificationof the offer of green corrosion inhibitors for the chemical treatment of heat exchangers.